The Role of Iron in Atherosclerosis in Apolipoprotein E Deficient Mice - Ma, Juan; Ma, Hui-Min; Shen, Meng-Qi; Wang, Yuan Yuan; Bao, Yu-Xin; Liu, Yong; Ke, Ya; Qian, Zhong-Ming (Frontiers in Cardiovascular Medicine, 2022)
The role of iron in atherosclerosis is still a controversial and unsolved issue. Here, we investigated serum iron, expression of iron regulatory, transport and storage proteins, pro-inflammatory chemokines and cytokines in ApoE–/– mice. We demonstrated that ApoE–/– induced atherosclerosis and an increase in iron contents, expression of transferrin receptor 1 (TfR1), iron regulatory proteins (IRPs), heme oxygenase 1 (HO1), cellular adhesion molecules and pro-inflammatory cytokines, production of reactive oxygen species (ROS), and a reduction in expression of superoxide dismutase and glutathione peroxidase enzyme in aortic tissues. All of these changes induced by ApoE deficiency could be significantly abolished by deferoxamine. The data showed that the increased iron in aortic tissues was mainly due to the increased iron uptake via IRP/TfR1 upregulation. These findings plus a brief analysis of the controversial results reported previously showed that ApoE deficiency-induced atherosclerosis is partly mediated by the increased iron in aortic tissues.